Updating the proteome of the uncultivable hemotrophic Mycoplasma suis in experimentally infected pigs. Issue 4 (18th February 2016) - Dietz, Stefanie; Lassek, Christian; Mack, Sarah‐Lena; Ritzmann, Mathias; Stadler, Julia; Becher, Dörte; Hoelzle, Katharina; Riedel, Katharina; Hoelzle, Ludwig E.
Abstract : Mycoplasma suis belongs to the hemotrophic mycoplasmas that are associated with acute and chronic anemia in a wide range of livestock and wild animals. The inability to culture M. suis in vitro has hindered its characterization at the molecular level. Since the publication of M. suis genome sequences in 2011 only one proteome study has been published. Aim of the presented study was to significantly extend the proteome coverage of M. suis strain KI_3806 during acute infection by applying three different protein extraction methods followed by 1D SDS‐PAGE and LC‐MS/MS. A total of 404 of 795 M. suis KI_3806 proteins (50.8%) were identified. Data analysis revealed the expression of 83.7% of the predicted ORFs with assigned functions but also highlights the expression of 179 of 523 (34.2%) hypothetical proteins with unknown functions. Computational analyses identified expressed membrane‐associated hypothetical proteins that might be involved in adhesion or host–pathogen interaction. Furthermore, analyses of the expressed proteins indicated the existence of a hexose‐6‐phosphate‐transporter and an ECF transporter. In conclusion, our proteome study provides a further step toward the elucidation of the unique life cycle of M. suis and the establishment of an in vitro culture. All MS data have been deposited in the ProteomeXchange with identifier PXD002294 (http://proteomecentral.proteomexchange.org/dataset/PXD002294 ).